1990
DOI: 10.1161/01.res.66.4.913
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning slows energy metabolism and delays ultrastructural damage during a sustained ischemic episode.

Abstract: We have shown previously that preconditioning myocardium with four 5-minute episodes of ischemia and reperfusion dramatically limited the size of infarcts caused by a subsequent 40-minute episode of sustained ischemia. The current study was undertaken to assess whether the same preconditioning protocol slowed the loss of high energy phosphates, limited catabolite accumulation, and/or delayed ultrastructural damage during a sustained ischemic episode. Myocardial metabolites and ultrastructure in the severely is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
276
2
14

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 709 publications
(316 citation statements)
references
References 33 publications
18
276
2
14
Order By: Relevance
“…Instead such preconditioning protects the heart from subsequent ischemic injury (Murry et al, 1990). Recently, Gyongyosi et al (2010) have shown that HPC enhances migration and recruitment of hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) to infarcted myocardium in a porcine myocardial ischemiareperfusion model.…”
Section: Signaling Factors and Pathways Involved In Migration Of Cscsmentioning
confidence: 99%
“…Instead such preconditioning protects the heart from subsequent ischemic injury (Murry et al, 1990). Recently, Gyongyosi et al (2010) have shown that HPC enhances migration and recruitment of hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) to infarcted myocardium in a porcine myocardial ischemiareperfusion model.…”
Section: Signaling Factors and Pathways Involved In Migration Of Cscsmentioning
confidence: 99%
“…[171][172][173][174] A signature of preconditioned myocardium in the canine model is slowed ATP depletion and lactate accumulation during the sustained episode of ischemia. 175 This characteristic of slowed energy utilization by preconditioned tissue may be related to the mechanism whereby ischemic preconditioning delays cell death. Murry et al 175 pointed out that preconditioned tissue also exhibits a high creatine phosphate concentration, more intracellular glucose, less glycogen, and a smaller adenine nucleotide pool, contains more Kϩ, and is somewhat edematous.…”
Section: Biology Of Preconditioningmentioning
confidence: 99%
“…Preconditioning refers to the observation that brief periods of myocardial ischemia provide protection against subsequent ischemia/reperfusion injury. 27 The effect of preconditioning can be mimicked by adenosine agonists. Preconditioning is abolished in the presence of adenosine receptor antagonists.28 Thus, the augmented adenosine release in the presence of the three antioxidants could have a conditioning effect on neighboring microvascular regions not yet ischemic.…”
Section: Adenosinementioning
confidence: 99%